Escaping from American intelligence: culture, ethnocentrism and the Anglosphere - ALDRICH, RICHARD J.; KASUKU, JOHN (International Affairs, 2012)
The United States and its closest allies now spend over $100 billion a year on intelligence. Ten years after 9/11, the intelligence machine is certainly bigger—but not necessarily better. American intelligence continues to privilege old-fashioned strategic analysis for policy-makers and exhibits a technocratic approach to asymmetric security threats, epitomized by the accelerated use of drone strikes and data-mining. Distinguished commentators have focused on the panacea of top-down reform, while politicians and practitioners have created entirely new agencies. However, these prescriptions for change remain conceptually limited because of underlying Anglo-Saxon presumptions about what intelligence is. Although intelligence is a global business, when we talk about intelligence we tend to use a vocabulary that is narrowly derived from the experiences of America and its English-speaking nebula. This article deploys the notion of strategic culture to explain why this is. It then explores the cases of China and South Africa to suggest how we might begin to rethink our intelligence communities and their tasks. It argues that the road to success is about individuals, attitudes and cultures rather than organizations. Future improvement will depend on our ability to recognize the changing nature of the security environment and to practise the art of ‘intelligence among the people’. While the United States remains the world's most significant military power, its strategic culture is unsuited to this new terrain and arguably other countries have adapted to it better.